2021
DOI: 10.1038/s41598-021-92766-z
|View full text |Cite
|
Sign up to set email alerts
|

Mobility restrictions were associated with reductions in COVID-19 incidence early in the pandemic: evidence from a real-time evaluation in 34 countries

Abstract: Most countries have implemented restrictions on mobility to prevent the spread of Coronavirus disease-19 (COVID-19), entailing considerable societal costs but, at least initially, based on limited evidence of effectiveness. We asked whether mobility restrictions were associated with changes in the occurrence of COVID-19 in 34 OECD countries plus Singapore and Taiwan. Our data sources were the Google Global Mobility Data Source, which reports different types of mobility, and COVID-19 cases retrieved from the da… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
66
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(71 citation statements)
references
References 26 publications
3
66
1
1
Order By: Relevance
“…At this time, public facilities such as schools, o ces, houses of worship were closed, so social gatherings were prohibited (20). This nding was consistent with previous studies, which found that restricting public mobility was associated with a decrease in SARS-CoV-2 transmission (21)(22)(23). However, the rates sharply rose ten times in September 2020 as the government replaced PSBB with a new normal policy (TNBPAC) since the end of June 2020.…”
Section: Discussionsupporting
confidence: 91%
“…At this time, public facilities such as schools, o ces, houses of worship were closed, so social gatherings were prohibited (20). This nding was consistent with previous studies, which found that restricting public mobility was associated with a decrease in SARS-CoV-2 transmission (21)(22)(23). However, the rates sharply rose ten times in September 2020 as the government replaced PSBB with a new normal policy (TNBPAC) since the end of June 2020.…”
Section: Discussionsupporting
confidence: 91%
“…With 'stay-at-home' orders and recommendations, the ways of carrying out the city's activities such as education, work, shopping, or leisure, changed. Mobility within the city space [8][9][10][11] as well as the public transportation were significantly reduced. Various lockdown-related measures, such as curfew, cordon sanitaire, or quarantine, were established at the scale of a whole city, a neighborhood, or a single building, depending on epidemiological situation.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it has been one of the primary forms of outbreak control in the early stage of COVID-19, along with screening and treatment while vaccine trials were under development [ 2 ]. Non-pharmaceutical interventions – including case isolation, voluntary home quarantine by active case finding and extensive contact tracing, and closure of schools and workplaces – have resulted in the reduction of COVID-19 transmission, mortality rates, and healthcare burden [ 3 5 ].…”
Section: Introductionmentioning
confidence: 99%